The Evaluation of Leukocytes in Response to the In Vitro Testing of Ventricular Assist Devices. Issue 9 (27th August 2013) - Chan, Chris H.H.; Hilton, Andrew; Foster, Graham; Hawkins, Karl M.; Badiei, Nafiseh; Thornton, Catherine A.
Abstract Infection is a clinically relevant adverse event in patients with ventricular assist device (VAD) support. The risk of infection could be linked to a reduced immune response resulting from damage to leukocytes during VAD support. The purpose of this study was to develop an understanding of leukocyte responses during the in vitro testing of VADs by analyzing the changes to their morphology and biochemistry. The VentrAssist implantable rotary blood pump (IRBP) and RotaFlow centrifugal pump (CP) were tested in vitro under constant hemodynamic conditions. Automated hematology analysis of samples collected regularly over 25‐h tests was undertaken. A new flow cytometric assay was employed to measure biochemical alteration, necrosis (7‐AAD) and morphological alteration (CD45 expression) of the circulating leukocytes during the pumping process. The results of hematology analysis show the total leukocyte number and subset counts decreased over the period of in vitro tests dependent on different blood pumps. The percentage of leukocytes damaged during 6‐h tests was 40.8 ± 5.7% for the VentrAssist IRBP, 17.6 ± 5.4% for the RotaFlow CP, and 2.7 ± 1.8% for the static control (all n = 5). Flow cytometric monitoring of CD45 expression and forward/side scatter characteristics revealed leukocytes that were fragmented into smaller pieces (microparticles). Scanning electron microscopy and imaging flow cytometry were used to confirm this. Device developers could use these robust cellular assays to gain a better understanding of leukocyte‐specific VAD performance.